2019
DOI: 10.1016/j.energy.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

R450A and R513A as lower GWP mixtures for high ambient temperature countries: Experimental comparison with R134a

Abstract: In recognition of the impact of the refrigeration sector on climate change, global commitments are achieved to replace hydrofluorocarbon substances with more planet-friendly alternatives. In this regard, countries with high ambient temperatures (HAT) face additional problems in identifying suitable alternatives due to the impact of such temperatures on energy performance in vapor compression systems. This paper presents an experimental analysis using R134a and two lower global warming potential (GWP) mixtures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(32 citation statements)
references
References 19 publications
(17 reference statements)
1
27
0
3
Order By: Relevance
“…Therefore, they are refrigerants that are mixed with HFCs [29][30][31], HFOs [32][33][34], and HCs [35][36][37]. Natural refrigerants are low-GWP, zero-ODP, high-capacity, low-pressure, and nontoxic [38][39][40]. Refrigerants need to be low-GWP, zero-ODP, high-capacity, low-pressure, and nontoxic, and should thus be mixed with HCs and HFOs; however, current refrigerants are still highly flammable and have low capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they are refrigerants that are mixed with HFCs [29][30][31], HFOs [32][33][34], and HCs [35][36][37]. Natural refrigerants are low-GWP, zero-ODP, high-capacity, low-pressure, and nontoxic [38][39][40]. Refrigerants need to be low-GWP, zero-ODP, high-capacity, low-pressure, and nontoxic, and should thus be mixed with HCs and HFOs; however, current refrigerants are still highly flammable and have low capacity.…”
Section: Introductionmentioning
confidence: 99%
“…The R134A, is a generation of HFC that possess zero ODP and a GWP = 1800 [14], that was developed for the R22, but it has a low refrigerant effect. The R513A, R515A, R450A, R456A were developed to be alternatives to R134, but the performances of all refrigerants were nearly [15][16][17][18], subsequently, the refrigerant developed to the R404A. The fourth generation R404A was the baseline for this research, and is currently the most used refrigerant, as shown Figure 5 below [7].…”
Section: Evolution Of the Refrigerantmentioning
confidence: 99%
“…The R134A, is a generation of HFC that possess zero ODP and a GWP = 1800, that was developed for the R22, but it has a low refrigerant effect [38]. The R513A, R515A, R450A, R456A were developed to be alternatives to R134, but the performances of all refrigerants were nearly, subsequently, the refrigerant developed to the R404A [11][12][13][14]. The fourth generation R404A was the baseline for this research, and is currently the most used refrigerant, as shown Figure 5 below [6].…”
Section: Evolution Of the Refrigerantmentioning
confidence: 99%